2021
DOI: 10.1177/0265659021995543
|View full text |Cite
|
Sign up to set email alerts
|

Dual-qualified teachers and speech-language therapists reflect on preparation and practice in school-based language and literacy

Abstract: Internationally, professional bodies are increasingly recognizing a role for speech-language therapists (SLTs) in identifying and supporting students who struggle with literacy. Although some guidelines have been developed to support this work, little is understood about the overlapping, but distinctive knowledge bases claimed by SLTs and teachers with respect to reading instruction and provision of additional support to struggling readers. In this article, we report on a qualitative exploration of the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Alongside these dominant ineffective practices in Australian classrooms is the concern that many Australian teachers have not been sufficiently prepared with knowledge of evidence-based reading instruction (Buckingham & Meeks, 2019;McLean, et al 2021). This lack of knowledge may impact on a teacher's ability to effectively teach reading and to accurately identify the need for targeted intervention in subcomponent reading skills (Graham et al, 2020;Hammond, 2015;Tetley & Jones, 2014).…”
Section: Inadequate Reading Instruction In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside these dominant ineffective practices in Australian classrooms is the concern that many Australian teachers have not been sufficiently prepared with knowledge of evidence-based reading instruction (Buckingham & Meeks, 2019;McLean, et al 2021). This lack of knowledge may impact on a teacher's ability to effectively teach reading and to accurately identify the need for targeted intervention in subcomponent reading skills (Graham et al, 2020;Hammond, 2015;Tetley & Jones, 2014).…”
Section: Inadequate Reading Instruction In Schoolsmentioning
confidence: 99%
“…According to Buckingham and Meeks (2019), none of the six most frequently prescribed textbooks in Australian initial teacher education literacy units "contained sufficiently accurate and detailed content that would allow graduate teachers to use effective, evidence-based instruction, and many contained information that was inadequate and/or misleading" (p. vi). Indeed, a recent study by McLean et al (2021) found that teachers overwhelmingly reported dissatisfaction with their pre-service teacher education courses and the "limited or non-existent focus on evidence-based reading instruction" (p. 11). This lack of effective pre-service teacher training in evidence-based reading instruction leaves the building of teacher capacity in the hands of schools, where knowledge, skills, and resources to achieve this are limited (Hempenstall, 2012).…”
Section: Inadequate Pre-service Teacher Educationmentioning
confidence: 99%
“…The former recommendations strengthen the case for interprofessional education (IPE) at undergraduate level, whereby early exposure to other disciplines is secured, perspectives are widened, knowledge and skills are shared, understanding of roles is increased, stereotypes are reduced and intervention models that incorporate exchanging of ideas and blending of professional roles are promoted (WHO, 2010; Wilson et al, 2015). Likewise, IPE may help to address the documented knowledge gap between teachers and SLTs about how best to support language and literacy development in order to secure optimal child outcomes (McLean et al, 2021).…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Schools, where teachers are employed, and health services, where SLTs are typically employed, have distinguishable frameworks of operation, practices, priorities and expectations (Law, 2000). It is suggested that SLTs’ positioning as a healthcare profession within a medical model frequently results in SLTs’ theories and practice being rooted more in scientific investigation and empirical evidence than their teaching colleagues, whose theory and practice has its foundations nested more within social constructivism (McLean et al, 2021; Snow, 2016). In addition to diverse theoretical and practical perspectives, McLean et al’s (2021) recent exploration of professionals working in schools who are dual-qualified SLTs and teachers confirmed findings of others that there also appears to be a knowledge gap between teachers and SLTs in relation to supporting language and literacy development.…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, SLTs were perceived to be reasonably knowledgeable about the characteristics of these conditions, but evaluation and intervention plans were often structured according to incorrect information, which negatively affects therapy outcomes (Yilmaz 2021). A study conducted in Australia also identified superior linguistic knowledge levels amongst dually qualified SLT teachers, but restricted awareness of aspects relating to literacy was highlighted (McLean, Snow & Serry 2021). In 2010, the American Speech-Language-Hearing Association (ASHA) reported that 91% of SLTs were unfamiliar with disciplinary literacy (Davis & Murza 2019).…”
Section: Introductionmentioning
confidence: 99%